If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -28 = x + -2x + -7 Reorder the terms: -28 = -7 + x + -2x Combine like terms: x + -2x = -1x -28 = -7 + -1x Solving -28 = -7 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -28 + x = -7 + -1x + x Combine like terms: -1x + x = 0 -28 + x = -7 + 0 -28 + x = -7 Add '28' to each side of the equation. -28 + 28 + x = -7 + 28 Combine like terms: -28 + 28 = 0 0 + x = -7 + 28 x = -7 + 28 Combine like terms: -7 + 28 = 21 x = 21 Simplifying x = 21
| 23/5+87/14= | | 14.4-5=9 | | 10.2-7.3x=-58 | | 13.95-5=9 | | 7y+2(y-5)=5(y+2)-5 | | 3w^2-23w-13=0 | | 5(2q)+(q-4)+q=5 | | 9x+5y+0.1z=100 | | 2(6)(h)+2(h)(17)+2(6)(17)=342 | | 6x=x+6 | | 2(6)(h)+2(h)(17)+2(6)(17)=h | | 12.5y+30+130-30=180 | | 13x-30=100 | | 9r=81 | | (2k+1)(2m+1)= | | -2-ln(x+1)=0 | | 20x^2-2x-4=0 | | 72x^2+96x-936=0 | | 4x+-6=34 | | -2x-(-8+3x)=6 | | y=-3x+-8 | | 3x+12-7*3x=123 | | (y+7)(y-8)= | | 72x^2-2496x-936=0 | | 98-7(10)= | | 98-7(-5)= | | (8x+1)-(-5x+5)= | | 98-7(280)= | | 2x^2-18x+45=0 | | y=5E-06x+0.24 | | 11=18-x | | (7x+5)+(-8x+6)= |